CDHA Ceramic Microspheres for Periodontitis Treatment: Synthesis, Characterization and Doxycycline Release Profiles - Sunita Prem Victor; TS Sampath Kumar (The Indonesian Journal of Dental Research, 2011)
The present study is focused on the development of doxycycline loaded calcium–deficient hydroxyapatite (CDHA) microspheres for the treatment of periodontitis. The CDHA microspheres were formed by liquid immiscibility effect using gelatin and paraffin oil with varying Ca/P ratios using calcium hydroxide and diammonium hydrogen orthophosphate as precursors. The morphology of the microspheres as characterized by SEM was optimized by varying the gelatin content. The doxycycline incorporation and its release profiles were studied by UV-Visible spectroscopy in phosphate buffer at physiological conditions. The pH of the buffer solution was initially optimized to have maximum amount of drug loading. Doxycycline loading around the physiological pH of 7 has the highest amount of drug incorporation. All the microspheres exhibit similar release profiles with an initial gradual increase reaching a maximum value and then nearly constant release. The microspheres formed using 6% gelatin shows maximum amount of drug release of 80%.